Implementasi Sistem Robot Otonom dengan Sensor Kinect menggunakan Algoritme Gmapping dan Timed Elastic Band - Hamdan Zuhdi Dewanul Arifin; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The isolation room in the hospital has very strict safety and health procedures to maintain the sterility of the area. This requires health workers to use personal protective equipment (PPE) during their activities in the isolation room. The virus outbreak in 2020 made hospitals need more isolation rooms, resulting in higher demand for PPE supplies and a higher risk of health workers being exposed to the virus. For this, an autonomous mobile robot system is needed at the hospital to help the workforce, especially in terms of logistics. The system consists of several components including Kinect sensor, encoder, IMU, and with Robot Operating System (ROS) middleware. The advantage of this research is the shape of the robot prototype which has a large size. To create autonomous navigation, a path planning method is needed, therefore the Timed Elastic Band (TEB) algorithm is used. Before navigating, a precise map is needed, therefore a map-making method using the GMapping algorithm is needed. The test results on navigation show an accuracy of 50% from 10 trials that have been successful 5 times. Navigation is carried out using the TEB algorithm computation time of 2.77 seconds and the average time of successful robot movement to the destination coordinates is 129.98 seconds. For mapping, the accuracy is 50% with map size accuracy of 98.84%.